The genre regime of research evaluation: contradictory systems of value around academics' writing. (2nd November 2018) - Tusting, Karin
Abstract: This article addresses how academics navigate different kinds of prestige and different systems of value around what 'counts' in academic writing, focusing particularly on the impact of the genre regime associated with research evaluation in the UK Research Excellence Framework (REF). It draws on data from an Economic and Social Research Council (ESRC)-funded project working with academics across different disciplines and different institutions in England. We interviewed people about their writing practices several times, exploring their practices, life histories, institutional contexts, and the tools and resources they draw on as they write. Academics' research writing is framed within explicit institutional and departmental strategies around the numbers and publication venues of research outputs, driven by institutions' need to succeed in the national competitive research evaluation system. Such institutional strategies do not always map well onto other values systems in which academics have been trained and within which they locate themselves. The articles analyses the interviews we carried out, exploring how academics negotiate tensions between these systems of value and considering the implications of this for what is considered to be important in academic work and, therefore, what it means to be an academic.